Strategy of Value Averaging for Private Investor on Russian Stock Exchange - A. I. Bolvachev; A. R. Zamalov (Вестник Российского экономического университета имени Г. В. Плеханова)
The Russian stock exchange revived and began its energetic development in 1991 and it was connected with economy liberalization. Thus we can say that modern history of the Russian stock exchange embraces about 30 years, while in global practice the first stock exchange was born in 1661 in Amsterdam. The most progressive, according to numerous international investors, American stock exchange started functioning in 1791. This short history of the Russian stock exchange development could explain low finance literacy of the population. In spite of fast growth in the number of registered broker’s accounts on the Moscow exchange, a lot of investors in Russia prefer to redistribute a considerable proportion of their resources in foreign currency, gold, real estate. Such fund distribution cannot be explained only by low finance literacy. The Russian stock exchange demonstrates high volatility as, according to global rating agencies, it is emerging. However, stock exchange can be an appealing tool of investment, in case clear and high-quality strategies are used. Within the frames of the article the use of averaged value strategy on the Russian stock exchange is studied, at the same time it is compared with other popular strategies of long-term investment, such as strategy of equal amount purchase, strategy of buying the same number of securities.